SPK Untuk Memilih Metodologi Pengembangan SI (Studi Kasus : STMIK Atma Luhur) - Hilyah Magdalena (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Development needs for the changes and development of information systems. Information system development methodology that varies with the advantages and disadvantages of each to make the process of selecting information system development methodology to be not easy.to generate the development of information systems most appropriate for Atma STMIK Luhur, this study provides a structured hierarchy with methods Analytical Hierarchy Process (AHP), which displays the criteria - criteria for what should be considered in selecting information systems development methodologies. The results of respondent data processing expert with Expert Choice 2000 software indicates that the information system development methodology that works best for Noble STMIK Atma is an object-oriented methodology or OOAD (Object Oriented Analysis and Design) with the weight reached 23.9%. The first level of criteria most important to consider in selecting information systems development methodology is the criteria for the stages of system development, reaching 34.3% by weight.Keywords: Information System Development Methodology, Analytical Hierarchy Process (AHP), Expert Choice 2000, OOAD.